Trajectories Tracking Control for Rotary Inverted Pendulum using Backstepping Method - Pham, Ha-Gia-Bao; Nguyen, Huy-Khai; Nguyen, Tran-Quoc-Tuan; Nguyen, Van-Dong-Hai; Dao, Ngoc-Quy; Ngo , Van-Quy-Hai; Tran, Thanh-Son; Phan, Hien-Dat; Chu, Gia-Huy; Huynh, Hoang-Tien-Phat (Journal of Fuzzy Systems and Control, 2025)
Rotary inverted pendulum (RIP) is a fundamental yet challenging benchmark system in control engineering due to its nonlinear dynamics, instability, and underactuated nature. This study addresses the problem of trajectory tracking control for RIP, which is critical for ensuring system stability and accurate motion control in various engineering applications. Simulation results demonstrate that the backstepping approach achieves superior performance in terms of tracking accuracy, robustness, and convergence speed compared to traditional methods. The findings emphasize the effectiveness of backstepping in addressing control challenges in nonlinear systems, offering insights for future research in both theoretical advancements and real-world applications.